Pemanfaatan Ekstrak Buah Pinang (Areca catechu L.) Sebagai Sensitizer Pada Dye-Sensitized Solar Cell (DSSC) - Iin Novianty Iin; Asri Saleh Asri; Cherry Malika Bogra Cherry (Universitas Bojonegoro, 2026)
Dye Sensitized Solar Cell (DSSC) was one of the renewable energy technologies that utilizes sunlight as an energy source. The main component that plays a very important role in this system was dye or coloring agent because the dye functions as a sensitizer that absorbs light energy and transfers electrons to the semiconductor (TiO?) so that it greatly determines the efficiency value. In this study, areca nut was used as a source of natural dyes containing anthocyanin compounds. This study aims to determine the optimum pH of the thick extract of areca nut (Areca catechu L.) as a dye sensitizer and to determine the efficiency value of DSSC from areca nut extract with variations in pH buffers of 1, 3, 5, 7, 9, 11 and 13. The method used to obtain the extract was the maceration method for 3x24 hours using 96% ethanol and to spread TiO2 on the ITO glass using the doctor blade method with a glass size of 1 cm × 1 cm. The extract yield value obtained was 25.86% from 500 g of areca nut powder. Then, the highest efficiency value was obtained at pH 1 on the third day at 0.832% with a voltage of 563 mV and a current of 85.3 ?A. Analysis of the pH 1 dye was carried out using UV-Vis, obtaining a wavelength of 452 nm with an absorbance of 1.539. The surface morphology of the TiO2 layer added with pH 1 extract using SEM showed small pores that were evenly distributed and there were cracks and there were also lumps on the surface.